A STUDY ON SUSTAINABILITY OF EDUCATION DURING COVID19 IN INDIA - Ishpreet Kaur Saini (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The Covid19 had a widespread impact on each and every element of the world. One such impact has been faced by the educational institutions. The Objective of the study is to understand the effect of UGC and MOE Guidelines on the educational institutes that ultimately affected the learning in India. The collection of primary data was done in the form of a survey through Google form, the number of valid responses received for the study were 421. Further in order to examine the sample size the software named G*Power 3.1.9.2 was applied. The software determined 262 sample size and 421 responses were considered for the present research work. The respondents were from Pan India. In order to analyze the structural equation model, the software used was SmartPLS. Further the same was used to test the Research Hypothesis. As practical implications the government must try to make efforts in order to reduce the equity gaps affecting the learning of the students. The study is helpful in understanding the loopholes as well as the support required by the educational institutions from the government so as to improve the learning of the students in the country. Keywords: UGC, MOE, Educational Institutions, Learning